Fatal non-traumatic fat embolism - Mohtarrudin, Norhafizah; Itam @ Ismail, Iskasymar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Non-traumatic fat embolism (NTFE) is infrequently encountered in the clinical setting. The incidence of clinically detected fat embolism is less than 1%. It is diagnosed based on the evidence of fat emboli occluding the vessel lumen in a patient with no prior history of trauma. We report a case of NTFE in a lady who developed breathlessness and collapsed following home vaginal delivery. Post-mortem examination revealed extensive fat emboli in the pulmonary vessels. We elucidate the clinical challenges in diagnosing fat embolism (FE) in a patient without history of trauma.